Academic Integrity Outreach: supporting high school students for success in higher education - Morrow, Leeanne (Canadian Perspectives on Academic Integrity, 2018)
This brief article highlights how the Library at the University of Calgary works with high schools to teach their students about academic integrity with a focus on building ethical research and writing skills in advance of students' transition to a post-secondary learning environments.